Opportunistic Water-Borne Human Pathogenic Filamentous Fungi Unreported from Food - Novak Babič, Monika (2018)
Clean drinking water and sanitation are fundamental human rights recognized by the United Nations (UN) General Assembly and the Human Rights Council in 2010 (Resolution 64/292). In modern societies, water is not related only to drinking, it is also widely used for personal and home hygiene, and leisure. Ongoing human population and subsequent environmental stressors challenge the current standards on safe drinking and recreational water, requiring regular updating. Also, a changing Earth and its increasingly frequent extreme weather events and climatic changes underpin the necessity to adjust regulation to a risk-based approach. Although fungi were never introduced to water quality regulations, the incidence of fungal infections worldwide is growing, and changes in antimicrobial resistance patterns are taking place. The presence of fungi in different types of water has been thoroughly investigated during the past 30 years only in Europe, and more than 400 different species were reported from ground-, surface-, and tap-water. The most frequently reported fungi, however, were not waterborne, but are frequently related to soil, air, and food. This review focuses on waterborne filamentous fungi, unreported from food, that offer a pathogenic potential.